The Use of Contextual Teaching and Learning (CTL) in the Reading Course for English Education Students at Universitas Potensi Utama Medan - Amaniarsih, Dwi Suci; Meisuri, Meisuri (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
This study aims to explore the use of the Contextual Teaching and Learning (CTL) approach in teaching the reading course among English Education students at Universitas Potensi Utama Medan. CTL emphasizes the connection between learning materials and real-life contexts, which is expected to enhance students' motivation and understanding of reading texts. The research method employed is descriptive qualitative, involving students and lecturers as respondents. Data were collected through interviews, classroom observations, and document analysis. The findings indicate that the implementation of CTL in reading instruction significantly increases student engagement, conceptual understanding, and their ability to analyze texts. Additionally, students reported feeling more motivated and capable of relating the material to their personal experiences. This study recommends a broader implementation of CTL within the English. Education curriculum to improve the quality of teaching and student learning outcomes.